2022
DOI: 10.1021/acs.joc.2c02182
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 10-PhenanthrenolsviaPhotosensitized Triplet Energy Transfer, Photoinduced Electron Transfer, and Cobalt Catalysis

Abstract: Due to the inert redox activity and high triplet energy, radical chemistry of 1,3-dicarbonyl compounds usually requires prefunctionalization substrates, external oxidant, and high-energy UV light. Here, we report a visible-light-driven photocatalyst/cobaloxime system composed of a photosensitized energy transfer reaction (PEnT) and photoinduced electron transfer reaction (PET) and with an interrupted 6π-photocyclization/dehydrogenative aromatization in one pot to synthesize 10-phenanthrenols. Preliminary mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…All reported biphenyl β-ketoesters 1a – 1u , 1w – 1aa , 1ac – 1ah , and D 5 -1a were synthesized according to the literature, , and the NMR spectroscopy was consistent with those data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All reported biphenyl β-ketoesters 1a – 1u , 1w – 1aa , 1ac – 1ah , and D 5 -1a were synthesized according to the literature, , and the NMR spectroscopy was consistent with those data.…”
Section: Methodsmentioning
confidence: 99%
“…Recent blooming of visible light catalysis is crucial to the success of this easy manipulation and environmental begins transformation . More recently, we have successfully highlighted triplet biradical intermediate of ortho -biaryl-appended β-ketoesters that undergoes an interrupted 6π-photocyclization/dehydrogenative aromatization leading to 10-phenanthrenols without any external oxidants and with H 2 as the byproduct . In this context, we present below a new route to 9,10-dihydrophenanthren-9-ols under visible light irradiation.…”
Section: Introductionmentioning
confidence: 96%
“…A scope of 35 examples of CÀ H thiocyanation was reported in 40-95 % yield. Using this procedure, the authors disclose a broad array of β-ketoesters and 1,3-diketones capable of undergoing the reaction successfully including those bearing Michael acceptors (81), terminal alkynes (82), heterocycles (83), phosphonate (84), and thiolate ( 85) groups (Scheme 17B).…”
Section: Hydrogen Atom Transfermentioning
confidence: 99%
“…Niu and co-workers reported a benzannulation reaction initiated through an energy transfer (EnT) pathway using fac-Ir(ppy) 3 as a triplet sensitizer (Scheme 40A). [82] By employing a combination of fac-Ir(ppy) 3 and Co(dmgH) 2 PyCl in dichloromethane under blue light irradiation at room temperature, the researchers successfully obtained 42 different examples of functionalized 10-phenanthrenols with yields reaching up to 95 % (Scheme 40B). Mechanistic studies showed that the reaction is likely to be initiated by an EnT process to generate 1,2-biradical species I rather than the single-electron transfer process between the enol form of the starting material and the excited-state of the photocatalyst.…”
Section: Energy Transfer and Direct Excitationmentioning
confidence: 99%
See 1 more Smart Citation